Family Bonding Elements and Job Implication - Azan Ridzuan, Ahmad; Ong Hai Liaw, Jessica; Mazura Hj. Mohaiyadin, Norlaila; Azmi Mohd Zainol, Noor; Abdullah, Haslinda (International Journal of Engineering and Technology, 2018)
The family is the basic unit of society. The bonds between husband and wife, parents and children, are so firmly conceal in history and experience that often are lacking. The strength of family bonds is important to a family’s capacity to provide, promote, and care for its members. Frequent deployments, separations, and relocations are attributes of military life and can greatly affect military families. This study examines the correlation between family bonding elements and job implication using self-administered questionnaires gathered from 384 sample of Navy personnel and other ranks.  The quantitative research has been conducted on Navy personnel based at Lumut Naval Base, Perak. All the data’s collected has been analyzed by using SmartPLS version 3.2.5 path model analysis resulted four important findings: first, believe was significantly associated with job implication. Second, financial support was significantly associated with job implication. Third, communication skill was significantly associated with job implication. Fourth, family support was significantly associated with job implication. These results confirm that family bonding elements is vital and act as important determinant of job implication in the studied organization. Further, this study will be thoroughly offer discussion, and conclusion.